Múltiplas Trajetórias Dentro do Partido dos Trabalhadores (Santa Helena-PR): Militâncias e Memórias - Schmidt, Diná (2014)
Considering the moment experienced by the Brazilian politics, which has housed a PT (Workers Party) government for the last 12 years, this paper proposes a reflection on a less visualized face of the Workers Party. The spotlight of politics emphasizes characters that hold positions of government or management of the political party. Therefore, the aim of this work is to dialogue with militants who helped to build the proposal as well as the partisan institution, and contributed to spread the Workers Party s ideas and label as far away from the political centers of the country. These militants were essential for the strengthening and rising of the political party. The objects of study for this project are militants that campaigned for the PT in the city of St. Helena-PR from 1980 to 2013. From oral testimony, the paper reflects on their careers as activists, trying to understand how and why they were inserted in the PT, how they developed their militant experiences, and the meanings they attributed to these experiences through their narratives. Besides the importance of the trajectory of individual militants as participant in the Brazilian political history process, the set of all these trajectories helps to redirect the reflection of the political center for the "peripheries", equally important for a thorough analysis of the current political spectrum